Unveiling the Harrowing Realities : Kenyan Women Domestic Workers' Struggles for Freedom in Saudi Arabia - Bosibori, Catheline N. (Institute of African Studies, 2024)
Amidst economic challenges and soaring unemployment rates in Kenya, a significant number of young individuals have turned to migration in pursuit of temporary employment opportunities in Middle Eastern countries such as Dubai, Saudi Arabia, Qatar, and Jordan. Facilitated by employment agents who broker deals with Gulf-based employers, many of these migrants, predominantly comprising women, undergo brief, clandestine training periods in secluded Kenyan locations before assuming roles as domestic workers in the Gulf. Saudi Arabia has emerged as a primary destination for Kenyan women seeking domestic employment within the region. However, this trend has brought attention to the prevalent issues of abuse and dehumanizing treatment faced by foreign workers in the Kingdom. This paper delves into the journey of Kenyan women transitioning to employment in Saudi Arabia, documenting their work experiences, prevailing conditions, and the endurance of these slave-like circumstances. Emphasis is placed on the plight of Kenyan women engaged in domestic labor within Saudi Arabia. Employing a descriptive research design, this paper scrutinizes the exploitation of Kenyan women in the Gulf, utilizing firsthand accounts from returned victims of labor exploitation alongside secondary sources such as books, articles, newspapers, and video interpretations. The study contends that the ordeals faced by Kenyan women in Saudi Arabia constitute a violation of their freedom from exploitation. Using the globalization theory, dependency theory, and neo-Marxist perspectives, the article posits that the kafala system, coupled with the failure of both Kenyan and Saudi Arabian governments to safeguard these migrant domestic workers, perpetuates this form of modern labor exploitation. Moreover, ineffective bilateral labor agreements between Kenya and Saudi Arabia exacerbate the situation. To combat this egregious exploitation, the paper recommends fostering a cohesive partnership between the Kenyan government, recruitment agencies, and Gulf-based embassies. This alliance aims to proactively address and eliminate the systemic factors contributing to the perpetuation of exploitation experienced by Kenyan women in Saudi Arabia.
Keywords: Freedom from exploitation; Women; Saudi Arabia; Kenya; Abuse; Labor migration; international migration; East Africa; domestic employment; kafala system